If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2y + 3) + -4 = 9 Reorder the terms: (3 + 2y) + -4 = 9 Remove parenthesis around (3 + 2y) 3 + 2y + -4 = 9 Reorder the terms: 3 + -4 + 2y = 9 Combine like terms: 3 + -4 = -1 -1 + 2y = 9 Solving -1 + 2y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2y = 9 + 1 Combine like terms: -1 + 1 = 0 0 + 2y = 9 + 1 2y = 9 + 1 Combine like terms: 9 + 1 = 10 2y = 10 Divide each side by '2'. y = 5 Simplifying y = 5
| k=1.6d+300 | | 3q=18 | | 10z=9z-11 | | 41=5w-9 | | a+2(a-3)=15 | | 4+4x=-24 | | -6+2*y=0 | | j+6=9 | | 7x-15=4x-6 | | -2+2*y=0 | | 6=2p | | 2u-7=-19 | | 6+2*y=0 | | 173-w=224 | | 6(y-3)=6y+7 | | n/9=16/24 | | -11=4v+5 | | 4x^2-49+12=0 | | 4v-15=45 | | -5x=3y | | -6-2y=0 | | 3+4u=-25 | | 3X-15=7x+80 | | 46=3w+10 | | 9/n=4/8 | | -5x+5y=8 | | ln(4x-2)=24 | | x^3=(1/27) | | lnx=13 | | x/3.1=0.4 | | 0=3y^2+10 | | 8x+24=8(x+3) |